Designing and scaling up integrated youth mental health care. Issue 1 (11th January 2022) - McGorry, Patrick D.; Mei, Cristina; Chanen, Andrew; Hodges, Craig; Alvarez‐Jimenez, Mario; Killackey, Eóin
Abstract : Mental ill‐health represents the main threat to the health, survival and future potential of young people around the world. There are indications that this is a rising tide of vulnerability and need for care, a trend that has been augmented by the COVID‐19 pandemic. It represents a global public health crisis, which not only demands a deep and sophisticated understanding of possible targets for prevention, but also urgent reform and investment in the provision of developmentally appropriate clinical care. Despite having the greatest level of need, and potential to benefit, adolescents and emerging adults have the worst access to timely and quality mental health care. How is this global crisis to be addressed? Since the start of the century, a range of co‐designed youth mental health strategies and innovations have emerged. These range from digital platforms, through to new models of primary care to new services for potentially severe mental illness, which must be locally adapted according to the availability of resources, workforce, cultural factors and health financing patterns. The fulcrum of this progress is the advent of broad‐spectrum, integrated primary youth mental health care services. They represent a blueprint and beach‐head for an overdue global system reform. While resources will vary across settings, the mental health needs of young people are largely universal, and underpin a set of fundamental principles and design features. These include establishing an accessible, "soft entry" youth primary care platform with digital support, where young people are valued and essential partners in the design, operation, management and evaluation of the service. Global progress achieved to date in implementing integrated youth mental health care has highlighted that these services are being accessed by young people with genuine and substantial mental health needs, that they are benefiting from them, and that both these young people and their families are highly satisfied with the services they receive. However, we are still at base camp and these primary care platforms need to be scaled up across the globe, complemented by prevention, digital platforms and, crucially, more specialized care for complex and persistent conditions, aligned to this transitional age range (from approximately 12 to 25 years). The rising tide of mental ill‐health in young people globally demands that this focus be elevated to a top priority in global health.